2022
DOI: 10.3390/pharmaceutics14112279
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Efficiency of Mild-Temperature Photothermal Therapy for Cancer Assisting with Various Strategies

Abstract: Conventional photothermal therapy (PTT) irradiates the tumor tissues by elevating the temperature above 48 °C to exert thermal ablation, killing tumor cells. However, thermal ablation during PTT harmfully damages the surrounding normal tissues, post-treatment inflammatory responses, rapid metastasis due to the short-term mass release of tumor-cellular contents, or other side effects. To circumvent this limitation, mild-temperature photothermal therapy (MTPTT) was introduced to replace PTT as it exerts its acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 160 publications
0
13
0
Order By: Relevance
“…While the temperature of the PBS + light group did not exceed 40 °C even at the highest temperature, the PQ NP + light group exhibited an average temperature of around 50 °C. It was reported that a temperature over 43–44 °C induced heat erythema and over 48 °C induced thermal ablation. , Therefore, the PQ NP is expected to effectively suppress the tumors. After PTT on the mouse skin, the tissues were stained with H&E and TUNEL assay to observe the tissue damages induced by PTT (Figure S17).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the temperature of the PBS + light group did not exceed 40 °C even at the highest temperature, the PQ NP + light group exhibited an average temperature of around 50 °C. It was reported that a temperature over 43–44 °C induced heat erythema and over 48 °C induced thermal ablation. , Therefore, the PQ NP is expected to effectively suppress the tumors. After PTT on the mouse skin, the tissues were stained with H&E and TUNEL assay to observe the tissue damages induced by PTT (Figure S17).…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that a temperature over 43−44 °C induced heat erythema and over 48 °C induced thermal ablation. 57,58 Therefore, the PQ NP is expected to effectively suppress the tumors. After PTT on the mouse skin, the tissues were stained with H&E and TUNEL assay to observe the tissue damages induced by PTT (Figure S17).…”
Section: In Vivo Photothermal Therapy Effect Of Pq Npsmentioning
confidence: 99%
“…PTT, like PDT, is a new and non-invasive therapy that uses the conversion of light energy into heat energy to increase the temperature and achieve therapeutic effects at the lesion site [ 105 ]. PTT can be directly mediated by MOFs with inherent photothermal properties without the introduction of an exogenous PTA by using several PTAs as ligands (e.g., IR825 and ferrocene (Fc)) [ 7 ].…”
Section: Metal-organic Framework (Mofs)mentioning
confidence: 99%
“…Within 5 min, the temperature of the tumor site reached 65.5 °C, which has the ability to rapidly thermally ablate tumor cells. [41,42] The photographs of the tumor bearing mice before and after photothermal therapies were showed in Figure 7c, and the body weight changes of nude mice during treatment are recorded in Figure 7d. There was no significant difference in the body weight of nude mice before and after treatment.…”
Section: In Vivo Photothermal Efficiencymentioning
confidence: 99%